What is a Strike? - Langille, Brian (Canadian Labour & Employment Law Journal, 2009)
This paper looks into how a "strike" should be defined under Canadian law. Although labour boards and courts in Canada claim to apply an "objective" definition, whereby a "strike" means any con- certed cessation of work, the author argues that this approach is incap- able of providing a coherent answer to the question of which work stoppages are strikes and which are not. What is needed, rather, and what accurately reflects the understanding of "strike" embodied in labour relations statutes and cases decided at common law, is a subjec- tive definition that is based on the reason for the work stoppage. Thus, in the author's view, a strike is a timely (and hence legal) cessation of work if it is engaged in by a group of workers who are negotiating (or renego- tiating) their agreement with an employer, in an effort to induce the employer to come to terms. The author warns, however, that any attempt to constitutionalize the right to strike through the Charter freedom of association in s. 2(d), rather than through the guarantee of equality in s. 15, will inevitably draw courts into the mistaken exercise of trying to create a 'judicial labour code."